2001
DOI: 10.1051/lait:2001145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ripening temperature on the quality of low moisture Mozzarella cheese: 1. Composition and proteolysis

Abstract: Low-moisture Mozzarella cheese, in duplicate trials, was ripened at 0, 4, 10 or 15 o C for 70 d. For all temperature treatments, increasing ripening time resulted in significant (P < 0.05) increases in the level of proteolysis as measured by the levels of pH 4.6 soluble-N (pH 4.6SN) and 5% phosphotungstic acid-soluble N (PTA-N). Urea-PAGE electrophoretograms of the pH 4.6-insoluble cheese extracts showed that increasing the storage temperature resulted in an increase in the extent of degradation of α s1 -CN bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
40
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 30 publications
18
40
0
Order By: Relevance
“…The level of primary proteolysis in the control FFFS cheese (WSN~10-12 g.100 g −1 of total N at 45-60 days), as monitored using urea-PAGE and level of WSN, is typical of that previously reported for mozzarella stored at 4 or 8°C (Rudan et al 1999;Feeney et al 2001). The increase in proteolysis during ageing was affected by fat content, with fat reduction leading to a slower rate of degradation of α s1 casein and development of WSN in the full-salt cheese, and salt reduction.…”
Section: Discussionmentioning
confidence: 54%
“…The level of primary proteolysis in the control FFFS cheese (WSN~10-12 g.100 g −1 of total N at 45-60 days), as monitored using urea-PAGE and level of WSN, is typical of that previously reported for mozzarella stored at 4 or 8°C (Rudan et al 1999;Feeney et al 2001). The increase in proteolysis during ageing was affected by fat content, with fat reduction leading to a slower rate of degradation of α s1 casein and development of WSN in the full-salt cheese, and salt reduction.…”
Section: Discussionmentioning
confidence: 54%
“…Feeney et al [8], found that increasing the storage temperature for Mozzarella cheese from 0 to 15 o C, resulted in a higher level of degradation of α s1 -casein but had little effect on the extent of breakdown of β-casein. The increased hydrolysis of α s1 -casein coincided with increases of approximately 2.5 and 4.0 fold in the level of pH 4.6 soluble N and 5% phosphotungstic acid soluble N, respectively, at 70 d [8].…”
Section: Introductionmentioning
confidence: 99%
“…Feeney et al [8], found that increasing the storage temperature for Mozzarella cheese from 0 to 15 o C, resulted in a higher level of degradation of α s1 -casein but had little effect on the extent of breakdown of β-casein. The increased hydrolysis of α s1 -casein coincided with increases of approximately 2.5 and 4.0 fold in the level of pH 4.6 soluble N and 5% phosphotungstic acid soluble N, respectively, at 70 d [8]. Owing to the positive relationship between proteolysis and flowability in Cheddar cheese [1,14], altering the ripening temperature would be expected to affect the extent of age related changes in functionality, and hence the functional shelf life of low moisture (LM) Mozzarella cheese.…”
Section: Introductionmentioning
confidence: 99%
“…The mean protein content reported by other researchers was 26% (Feeney et al, 2001;Joshi et al, 2004;Banville et al, 2013).…”
Section: Figure 33 Variation Of Cheese Total Nitrogen (Tn%) Water Smentioning
confidence: 71%
“…The total calcium had a mean ± standard deviation of 0.5911 ± 0.0301% (Table 12). The total calcium levels in cultured low moisture mozzarella were 0.673% (Feeney et al, 2001). However, the total calcium levels in this study were close to that of 0.578%, which was obtained when the milk was pre-acidified to pH 5.8 with citric acid (Metzger et al, 2000a).…”
Section: Figure 34 Variation Of Cheese Fat In Dry Matter (Fdm %) Momentioning
confidence: 93%